A Genetic Algorithm Approach to the Container Loading Problem - Moura, Ana (2012)
The problem considered in this work is the Container Loading Problem. In this problem a set of rectangular boxes has to be packed in one rectangular container so that the available container space usage is maximized. The orientation constraints and the distinction between homogeneous and heterogeneous types of cargo are considered. We present the results obtained with a Genetic Algorithm approach. The good performance of this algorithm is shown by comparing them with well-known algorithms and results from the literature.